Configuration analysis of marine economic resilience based on 11 coastal provinces of China: an fsQCA approach - Liu, Dong; Huang, Zhenyu (Frontiers in Marine Science, 2024)
Introduction The marine economy has played an important role in stabilizing national economic growth and ensuring economic security. Achieving high-quality and sustainable development of the marine economy is a strategic task for China to build a maritime power. Confronting various risk factors such as financial crises, natural disasters, geopolitical conflicts, industrial transformation, and public health security, etc., marine economic resilience (MER) has received widespread attention in recent years and is considered to be crucial for high-quality and sustainable development of the marine economy. Methods This study takes 11 coastal provinces in China as cases, integrates 6 condition variables by building a Resistance capability-Recovery capability-Renewal capability (3R) configuration model, and uses the fuzzy-set qualitative comparative analysis (fsQCA) approach to empirically explore the configuration effect between multiple land factors and MER. Results and discussion (1) None of the 6 conditions in the three dimensions of resistance capability, recovery capability, and renewal capability alone constitute the necessary conditions for strong or weak MER, indicating that a single condition has weak explanatory power for MER; (2) There are two configurations for strong MER: Strong Resistance-Recovery Type and Comprehensive Strong Type. Industrial structure, governmental capability, and digital economy are the core conditions for strong MER configurations; (3) There are four weak MER configurations: Comprehensive Weak Type, Weak Recovery-Renewal Type, Weak Resistance-Recovery Type I, and Weak Resistance-Recovery Type II. This study may expand the research scope of MER influencing factors and enriching the research perspective of land-sea integration, as well as providing decision-makers with practical policy implications.